The Decline of Moral Intelligence in the Indonesian Advocate Profession: Causes, Impacts, and Reforms - Darwin Steven Siagian; Catharina Dewi Wulandari (UNISSULA, 2025)
Indonesia’s rule of law framework recognizes advocates as law enforcers, yet declining integrity appears when defending guilty clients without justice values. This research arises from ethical violations that reflect a moral crisis and the weakening of moral intelligence among advocates. The purpose of this study is to analyze the factors causing the decline of advocates’ integrity, assess the effectiveness of the professional code of ethics in maintaining morality, and propose solutions to strengthen the integrity of the legal profession in Indonesia. This study employs an interdisciplinary legal research method with a descriptive-analytical approach. Primary data were obtained through interviews with legal practitioners, while secondary data were derived from laws, legal literature, and the advocates’ code of ethics. Data were analyzed qualitatively by applying legal system theory, legal culture theory, morality theory, and legal certainty theory. The findings indicate that the main factors behind the decline in advocates’ integrity include misinterpretation of client loyalty, weak enforcement of the code of ethics, commercialization of the profession, and a permissive legal culture. The conclusion emphasizes that moral intelligence must be the foundation of the advocate profession. Reform in legal education, strengthening of the code of ethics, and regulatory renewal are required to restore advocates’ role as officium nobile.